Justin Martyr – between Philosophy and the Second Sophistic - Justinas Ambrazas (Literatūra (Vilnius))
Only relatively recently have researchers begun to speak more loudly about how studies on the Second Sophistic overlook Christian (and Jewish) literature. On the other hand, studies on early Christianity in turn view the Second Sophistic as an exclusively rhetorical movement. The aim of the article’s author is to look at Justin, a Christian philosopher, in the context of the Second Sophistic. The paper first discusses the Second Sophistic as a rhetorical, cultural, and sociopolitical movement. The article distinguishes between two groups of educated people of that time: philosophers and rhetoricians-sophists and discusses their distinguishing features. This study examines the influence of the Second Sophistic on philosophical discourse and the tension between rhetoric and philosophy. The author of the article also analyzes Justin Martyr’s self-representation techniques and participation in rhetorical and philosophical disputes, conflicts with contemporaries, and strategies for presenting Christian teachings. Finally, it is concluded that although Justin can be seen as one of the representatives of the Second Sophistic, his main goal was to proclaim the Christian message, which only further strengthens his role as an apologist.